Vertical hydraulic gradient research in hyporheic zone of Beberibe river in Pernambuco State (Brazil) - Veras,Tatiane Barbosa (2016)
ABSTRACT The interaction between groundwater and surface water occurs naturally and is dependent on the dynamics in the hyporheic zone. The hyporheic zone is the interface between the surface water source and the phreatic aquifer and it’s a system that also influences the water quality. An important feature is the ability to flux in this zone. This work aimed to evaluate the vertical hydraulic gradient in the hyporheic zone at two points in Beberibe river, Olinda-PE, to understand the hyporheic environment characteristics and water flow dynamics in experimental area, in addition to identify the existence of hydraulic connection between surface water and groundwater. The experimental phase consisted of infiltration tests in riverbed with cylinder infiltrometer and vertical hydraulic gradients readings with differential piezometer, complemented with grain size information, for an assessment of the water budget between the river and the aquifer. Analyzing the behavior of the interaction over the period of 10 months, it was observed that the Beberibe river (middle course) contributes to the groundwater recharge in most of the time. The average infiltration rate was 1.02 mm/min in point 1 and 0.85 mm/min in point 2. It was concluded that there is a variability in flow direction, which often is top-down, but may undergo change in the stream showing upstream after long periods of rainfall. Another conclusion is that grain size distribution of bed sediment, that is predominantly sandy, influences hydraulic conductivity of hyporheic zone and influences consequently the vertical flow rates.